2014
DOI: 10.1002/2014je004653
|View full text |Cite
|
Sign up to set email alerts
|

Stagnant lid convection in bottom-heated thin 3-D spherical shells: Influence of curvature and implications for dwarf planets and icy moons

Abstract: (2014), Stagnant lid convection in bottom-heated thin 3-D spherical shells: Influence of curvature and implications for dwarf planets and icy moons, J. Geophys. Res. Planets, 119, 1895-1913, doi:10.1002 Abstract Because the viscosity of ice is strongly temperature dependent, convection in the ice layers of icy moons and dwarf planets likely operates in the stagnant lid regime, in which a rigid lid forms at the top of the fluid and reduces the heat transfer. A detailed modeling of the thermal history and radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(73 citation statements)
references
References 35 publications
4
66
3
Order By: Relevance
“…Jarvis et al () explored the influence of relative core size on temperature and convective planform in isoviscous systems and found convection in cold spherical shells characterized by a single plume rising from the core when f is 0.3 or less. Yao et al () reported similar planforms with viscosity contrasts up to 10 5 but relatively low effective Rayleigh numbers. These authors derived parameterizations for the interior temperature and heat flux in variable core size spherical shell SLC (Yao et al, ) heated solely by an isothermal core.…”
Section: Introductionmentioning
confidence: 82%
“…Jarvis et al () explored the influence of relative core size on temperature and convective planform in isoviscous systems and found convection in cold spherical shells characterized by a single plume rising from the core when f is 0.3 or less. Yao et al () reported similar planforms with viscosity contrasts up to 10 5 but relatively low effective Rayleigh numbers. These authors derived parameterizations for the interior temperature and heat flux in variable core size spherical shell SLC (Yao et al, ) heated solely by an isothermal core.…”
Section: Introductionmentioning
confidence: 82%
“…Therefore, even lower‐reference viscosities or activation energies might be required. On the other hand, small cores tend to promote the formation of low‐degree (possibly degree‐one) structures in 3‐D isochemical thermal convection (Guerrero et al, ; Yao et al, ). The IBC overturn is driven by a compositional instability, which, as previously discussed in this section, is likely to grow according to a small wavelength comparable to the IBC thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the isoviscous cases, therefore, the internal temperature is generally higher (Figure b), and so is the internal heating ratio; the values of ξ are ∼0.47 and ∼0.76, respectively, for H ∗ of only 3 and 6. For purely basal heating and purely internal heating, various scaling relations are available [e.g., Moresi and Solomatov , ; Solomatov and Moresi , ; Reese et al , ; Deschamps and Lin , ; Yao et al , ], and it is straightforward to design a simulation with a desired combination of surface heat flux and internal temperature. For mixed heating, such relations are yet to be developed, and it requires some trial and error to control surface heat flux, internal temperature, and internal heating ratio.…”
Section: Basicsmentioning
confidence: 99%